2009
DOI: 10.1152/ajpregu.00263.2009
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein deficiency leads to soleus muscle contractile dysfunction following acute spinal cord injury in mice

Abstract: Laminectomy animals served as surgical controls. Mice in SCT groups experienced similar percent body mass (BM) losses at 7 days postinjury. Soleus muscle mass (MM) and MMto-BM ratio were lower at 7 days postinjury in SCT vs. laminectomy mice, with no differences observed between strains. However, soleus muscles from MT Ϫ/Ϫ trans mice showed reduced maximal specific tension compared with MT Ϫ/Ϫ lami animals. Mean cross-sectional area (m 2 ) of type I and type IIa fibers decreased similarly in SCT groups compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The relationship between mineral absorption (for zinc homeostasis) and metallothioneins was previously suggested for DMD (Mukund and Subramaniam, 2015), but this is the first time that this hypothesis is raised for TMD from our results. All MT-related DEGS found in our study are down-regulated -in a study by DeRuisseau, et al (DeRuisseau et al, 2009) it was seen that MT deficiency did not affect loss of muscle mass in soleus but resulted in contractile dysfunction and increased lipid peroxidation. The appearance of these pathways is reinforced by the appearance of biological processes related to cellular response to ions and cellular zinc ion homeostasis (Figure 4).…”
Section: Biological Process Classification and Kegg/reactome Pathway supporting
confidence: 46%
“…The relationship between mineral absorption (for zinc homeostasis) and metallothioneins was previously suggested for DMD (Mukund and Subramaniam, 2015), but this is the first time that this hypothesis is raised for TMD from our results. All MT-related DEGS found in our study are down-regulated -in a study by DeRuisseau, et al (DeRuisseau et al, 2009) it was seen that MT deficiency did not affect loss of muscle mass in soleus but resulted in contractile dysfunction and increased lipid peroxidation. The appearance of these pathways is reinforced by the appearance of biological processes related to cellular response to ions and cellular zinc ion homeostasis (Figure 4).…”
Section: Biological Process Classification and Kegg/reactome Pathway supporting
confidence: 46%
“…Spinal cord trauma results in a rapid and extensive oxidative stress. It has long been established that oxidative stress plays a critical role in the pathophysiology of SCI [27][28][29] Oxidative stress can result from increased reactive oxygen species (ROS) production, and/or from decreased ROS scavenging capability. The cells' natural protective system against the devastating actions of ROS includes the protective enzymes including SOD and other antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of metallothionein in muscle myotubes in vitro was, however, not associated with changes in oxidative activity (15). A separate in vivo study examined the effect of metallothionein deficiency after acute spinal cord injury and concluded that the absence of metallothionein neither exacerbates an oxidative stress response nor impacts muscle atrophy (16). These findings suggest that modulation of metallothionein in atrophy models does not play a major role in the oxidative status of the muscle, or in the mechanism inducing the atrophic process.…”
mentioning
confidence: 98%
“…Moreover, changes in subcellular distribution of zinc and generation of free zinc in cells play a role in development of diseases such as type II diabetes (23), cancer (24), and immune diseases (25). Previous studies demonstrated the lack of impact of MT silencing on oxidative state of skeletal muscle cells both in vitro and in vivo (15,16). We therefore asked whether MTs could have a role in skeletal muscle metabolism related to its ability to modify intracellular zinc level.…”
mentioning
confidence: 99%